Do the Benefits of Male Circumcision Outweigh the Risks? A Critique of the Proposed CDC Guidelines - Earp, Brian D. (Frontiers in Pediatrics, 2015)
The Centers for Disease Control and Prevention (CDC) have announced a set of provisional guidelines concerning male circumcision, in which they suggest that the benefits of the surgery outweigh the risks. I offer a critique of the CDC position. Among other concerns, I suggest that the CDC relies more heavily than is warranted on studies from Sub-Saharan Africa that neither translate well to North American populations nor to circumcisions performed before an age of sexual debut; that it employs an inadequate conception of risk in its benefit vs. risk analysis; that it fails to consider the anatomy and functions of the penile prepuce (i.e., the part of the penis that is removed by circumcision); that it underestimates the adverse consequences associated with circumcision by focusing on short-term surgical complications rather than long-term harms; that it portrays both the risks and benefits of circumcision in a misleading manner, thereby undermining the possibility of obtaining informed consent; that it evinces a superficial and selective analysis of the literature on sexual outcomes associated with circumcision; and that it gives less attention than is desirable to ethical issues surrounding autonomy and bodily integrity. I conclude that circumcision before an age of consent is not an appropriate health-promotion strategy.